2013
DOI: 10.1016/j.jped.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Maternal education level and low birth weight: a meta-analysis

Abstract: The hypothesis of similarity between the extreme degrees of social distribution, translated by maternal education level in relation to the proportion of low birth weight, was not confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
84
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 24 publications
13
84
2
8
Order By: Relevance
“…The results of our study oppose several studies in Brazil, Europe, Asia and North America, which found a higher risk of adverse perinatal outcomes among families of low socioeconomic class, education, and whose parents had manual jobs 13,[15][16][17][18][19]32,34,[40][41][42][43] . The main strength of this study is the use of a random population-based sample (a 1/3 of the births of São Luís' residents), which allows for generalization of the results for the general population of live births.…”
Section: Resultscontrasting
confidence: 91%
“…The results of our study oppose several studies in Brazil, Europe, Asia and North America, which found a higher risk of adverse perinatal outcomes among families of low socioeconomic class, education, and whose parents had manual jobs 13,[15][16][17][18][19]32,34,[40][41][42][43] . The main strength of this study is the use of a random population-based sample (a 1/3 of the births of São Luís' residents), which allows for generalization of the results for the general population of live births.…”
Section: Resultscontrasting
confidence: 91%
“…Previous research has documented that educated women are less likely to have an LBW baby and maternal education has a 33% protective effect against LBW (14). This has been observed in similar low-resource settings such as Nepal (15) and Bangladesh (16), and in a previous study from Pakistan (17).…”
Section: Discussionsupporting
confidence: 61%
“…Un meta-análisis realizado por Silvestrin et al 28 reportó que en Irán la diferencia en el bajo peso al nacer entre los hijos de mujeres sin educación, versus los recién nacidos de mujeres con mayor nivel educativo alcanzó 16,9% y 5,4%, respectivamente, el mismo estudio refiere que en Asia los niños de mujeres sin educación formal, versus las mujeres con secundaria o con un nivel educativo superior, presentan proporciones de 32% y 1,8% respectivamente de bajo peso al nacer.…”
Section: Discussionunclassified